Improving handover from intensive care to ward medical teams with simple changes to paperwork. Issue 1 (9th June 2015) - Messing, Jonathan
Abstract: Medical handover has been highlighted by the General Medical Council[1] as a critical step in patient care, ensuring continuity of care, patient safety, and enabling efficient multidisciplinary functioning. Handover between doctors on the intensive care team and the ward teams in the Great Western Hospital on step down was evaluated by assessing discharge summaries and patient notes, and by following up discharged patients. Handover was found to be present only in the minority of patients and documented in none. Simple changes were made to discharge paperwork in the form of a prompt and documentation of to whom handover was made, as well as the creation of space in the daily review sheets for patients with outstanding handover to be completed. The initial audit findings were presented at a local meeting to remind staff of the importance of handover. These simple modifications brought the handover rates up to 100% (n=12). The rates of documentation of handover also rose from 0% to 100%. This quality improvement project serves to demonstrate that carefully targeted, simple changes to practice in identified critical areas can produce dramatic as well as legally and ethically required results in a very short space of time.